The renal transport of hippurate and protein‐bound solutes. Issue 4 (25th February 2020) - Kumar, Rohit; Adiga, Avinash; Novack, Joshua; Etinger, Alex; Chinitz, Lawrence; Slater, James; de Loor, Henriette; Meijers, Bjorn; Holzman, Robert S.; Lowenstein, Jerome
Abstract: Measurement of the concentration of hippurate in the inferior vena cava and renal blood samples performed in 13 subjects with normal or near‐normal serum creatinine concentrations confirmed the prediction that endogenous hippurate was cleared on a single pass through the kidney with the same avidity as that reported for infused para‐amino hippurate. This suggests that a timed urine collection without infusion would provide a measure of effective renal plasma flow. Comparison of the arteriovenous concentration differences for a panel of protein‐bound solutes identified solutes that were secreted by the renal tubule and solutes that were subjected to tubular reabsorption. Abstract : The renal extraction of hippurate suggests that it can serve for the estimation of effective renal plasma flow without the need for infusion. The free (unbound) fraction of protein‐bound solutes are filtered at the glomerulus. Bound solutes are transported across the renal vascular bed, by organic anion transporters.